Understanding Sabiá virus infections (Brazilian mammarenavirus). Issue 48 (July 2022) - Nastri, Ana Catharina; Duarte-Neto, Amaro Nunes; Casadio, Luciana Vilas Boas; Souza, William Marciel de; Claro, Ingra M.; Manuli, Erika R.; Selegatto, Gloria; Salomão, Matias C.; Fialkovitz, Gabriel; Taborda, Mariane; Almeida, Bianca Leal de; Magri, Marcello C.; et al.
Abstract: Background: Only two naturally occurring human Sabiá virus (SABV) infections have been reported, and those occurred over 20 years ago. Methods: We diagnosed two new cases of SABV infection using metagenomics in patients thought to have severe yellow fever and described new features of histopathological findings. Results: We characterized clinical manifestations, histopathology and analyzed possible nosocomial transmission. Patients presented with hepatitis, bleeding, neurological alterations and died. We traced twenty-nine hospital contacts and evaluated them clinically and by RT-PCR and neutralizing antibodies. Autopsies uncovered unique features on electron microscopy, such as hepatocyte "pinewood knot" lesions. Although previous reports with similar New-World arenavirus had nosocomial transmission, our data did not find any case in contact tracing. Conclusions: Although an apparent by rare, Brazilian mammarenavirus infection is an etiology for acute hemorrhagic fever syndrome. The two fatal cases had peculiar histopathological findings not previously described. The virological diagnosis was possible only by contemporary techniques such as metagenomic assays. We found no subsequent infections when we used serological and molecular tests to evaluate close contacts.